Synthesis of several Urea plast Resins using Different Aldehydes Preparation of some Alkyde Resins and Empolyment of the prepared Resins as Additives for AZO Dyes - Baghdad Science Journal (مجلة بغداد للعلوم)
Urea formaldehyde resin was prepared by using basic media by yield 95%. The Remaining of ureaplasts resin were prepared in acetic acid media by high yield. Alkyde resins were prepared by condensation polymerization by react Succinic, Maleic, Phthalic anhydrides with Ethylene glycol or Glycerol. Select samples of the prepared alkyde resins were mixed with Azo dyes in special ratio. The mixtures were used as coatings for wood, and compaised with pure dyes. The Coating that some alkyde resins showed better adhesion from using dyes alone. Preparation of wood coating by mixing ureaplast resins and alkyde resins with Azo dyes in special ratios. The coating showed better adhesion, brighter colors and better resistance to heat from Preceding coat